Heterogeneity of serum gelatinases MMP‐2 and MMP‐9 isoforms and charge variants. Issue 2 (3rd December 2013) - Rossano, Rocco; Larocca, Marilena; Riviello, Lea; Coniglio, Maria Gabriella; Vandooren, Jennifer; Liuzzi, Grazia Maria; Opdenakker, Ghislain; Riccio, Paolo
Abstract The matrix metalloproteinases (MMPs) gelatinase A (MMP‐2) and gelatinase B (MMP‐9) are mediators of brain injury in multiple sclerosis (MS) and valuable biomarkers of disease activity. We applied bidimensional zymography (2‐DZ) as an extension of classic monodimensional zymography (1‐DZ) to analyse the complete pattern of isoforms and post‐translational modifications of both MMP‐9 and MMP‐2 present in the sera of MS patients. The enzymes were separated on the basis of their isoelectric points (pI) and apparent molecular weights (Mw) and identified both by comparison with standard enzyme preparations and by Western blot analysis. Two MMP‐2 isoforms, and at least three different isoforms and two different states of organization of MMP‐9 (the multimeric MMP‐9 and the N‐GAL‐MMP‐9 complex) were observed. In addition, 2‐DZ revealed for the first time that all MMP‐9 and MMP‐2 isoforms actually exist in the form of charge variants: four or five variants in the N‐GAL complex, more charge variants in the case of MMP‐9; and five to seven charge variants for MMP‐2. Charge variants were also observed in recombinant enzymes and, after concentration, also in sera from healthy individuals. Sialylation (MMP‐9) and phosphorylation (MMP‐2) contributed to molecular heterogeneity. The detection of charge variants of MMP‐9 and MMP‐2 in MS serum samples illustrates the power of 2‐DZ and demonstrates that in previous studies MMP mixtures, rather than single molecules, were analysed. These observations open perspectives for better diagnosis and prognosis of many diseases and need to be critically interpreted when applying other methods for MS and other diseases.